Bunch yield and genetic parameters of progenies between caiaué and African oil palm - Lopes, Ricardo; Cunha, Raimundo Nonato Vieira da; Resende, Marcos Deon Vilela de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the bunch yield and to estimate the genetic parameters of F1‑progenies between caiaué (Elaeis oleifera) and African oil palm (E. guineenses). The progenies were planted in plots with a variable number of plants. The number of bunches (NB), average bunch weight (ABW), and fresh fruit‑bunch yield (FFB) were evaluated, per plant, from the seventh to the thirteenth year after planting. These data were analyzed by REML/BLUP in 59 progenies, with a row‑and‑column unbalanced design. All characters showed a considerable genetic variability, with genetic variation coefficients between 18.1 and 25.5% for progenies, and 25.6 and 36.0% for individuals. Gains of more than 30%, for NB and FFB, and above 20% for ABW can be obtained selecting the five best progenies. By selecting the five best individuals, gains of more than 65% for NB and FFB, and above 60% for ABW, can be obtained. The progenies show a high‑genetic variability for bunch yield. High‑genetic gains can be obtained by selecting both for individuals, for clonal propagation, and for progenies, for seed propagation.